Unsweetening the Heart: Possible Pleiotropic Effects of SGLT2 Inhibitors on Cardio and Cerebrovascular Alterations in Resistant Hypertensive Subjects. (23rd November 2017) - Pioli, Mariana R; Ritter, Alessandra M V; Modolo, Rodrigo
Abstract: Resistant hypertension (RH) is a multifactorial disease associated with several target organ damage, such as microalbuminuria, left ventricular hypertrophy, and arterial stiffness. These subjects have high cardiovascular complications, especially when associated with diabetes condition. Sodium glucose cotransporter 2 (SGLT-2) inhibitors represent a new class of oral antidiabetic drugs that have shown positive effects in diabetics and even hypertensives subjects. Several studies demonstrated positive outcomes related to blood pressure levels, body weight, and glycemic control. Also found a reduction on microalbuminuria, cardiac and arterial remodeling process, and decrease in hospitalization care due heart failure. Despite these positive effects, the outcomes found for stroke were conflicted and tend neutral effect. Based on this, we sought to assess the pleiotropic effects of SGLT-2 inhibitors and the possible impact in RH subjects. In order to analyze the prospects of SGLT-2 inhibitors as a possible medication to complement the therapy manage of this high-risk class of patients.